Manajemen rantai pasokan dan implementasi sistem enterprise resources planning terhadap kinerja organisasi - Muthia Roza Linda; Akhyar Fauzi (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This study aims to determine the effect of supply chain management and the implementation of enterprise resource planning on organizational performance. The population and sample used in this study was employees of PT. Semen Padang is involved in the supply chain management process and runs an enterprise resource planning system. Data was collected through distributing questionnaires and data processing was carried out through SPSS 16.0 software. The results of this study indicate that supply chain management has a significant positive effect on organizational performance. The results of this study indicate that the implementation of enterprise resource planning on organizational performance has a significant positive effect on organizational performance.